Factors associated with abnormal glomerular filtration rate among HIV-positive children at the University of Maiduguri Teaching Hospital, Maiduguri, Nigeria - Ibrahim, Halima Umar; Rabasa, Adamu Ibrahim; Elechi, Hassan Abdullahi; Farouk, Abubakar Garba; Saidu, Isa Hassan; Maryah, Lawan Bukar (African Journal of Nephrology, 2018)
Background: Renal disease is commonly encountered in patients with HIV infection. The estimated glomerular filtration rate (eGFR) provides a good assessment of the renal function and is widely used in screening populations that are at risk of renal dysfunction. We determined the prevalence of abnormal eGFR among HIV-positive children and factors associated with it. Methods: In a cross-sectional study, children aged 15 years and below were recruited through systematic random sampling from the Paediatrics Infectious Disease Clinic of the University of Maiduguri Teaching Hospital until the desired sample size of 250 was reached. Clinical and laboratory information was obtained from the patient records and used for clinical staging and immunological classification. Serum creatinine was measured using Jaffe’s reaction and eGFR calculated using the Schwartz formula. The data obtained were analysed using SPSS version 16. Results: A total of 157 (62.8%) children were on antiretroviral therapy (HAART) for periods ranging from 1 to 168 months (mean duration 66.1 ± 46.5 months). Ninety-three (37.2%) children had advanced disease representing WHO clinical stages 3 and 4, whereas 103 (41.2%) had advanced or severe immunosuppression. The mean eGFR of the study population was 102 ± 41 mL/min/1.73 m2. Fifty-two children (20.1%) had low eGFR (<2 SD below the mean eGFR for age and sex) and 6 (2.4%) had high eGFR (>2 SD above the mean eGFR for age and sex). A total of 23 (9.2%) children had moderate to severe renal impairment, defined as eGFR <60 mL/min/1.73 m2. Age, sex, socio-economic status, mode of transmission as well as history of HAART usage were not significantly associated with abnormal eGFR. However, relatively shorter duration of treatment with HAART, as well as advanced clinical or immunological stage were all significantly associated with abnormal eGFR. Conclusion: Renal dysfunction is common among children with HIV disease in Maiduguri with over a third of those affected having moderate to severe renal dysfunction. Abnormal renal function is more frequent among children with advanced clinical and immunological disease. We recommend the regular determination of eGFR and early initiation of HAART in all children with HIV disease.